2019
DOI: 10.1371/journal.pone.0209181
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study and a post replication analysis revealed a promising genomic region and candidate genes for chicken eggshell blueness

Abstract: The eggshell blueness is an interesting object for chicken genetic studies and blue-shelled chicken industry, especially after the discovery of the causative mutation of chicken blue eggshell. In the present study, genome wide association study (GWAS) was conducted in Chinese Dongxiang blue-shelled chicken underlying four traits of blue eggshell pigments: quantity of biliverdin (QB), quantity of protoporphyrin (QP), quantity of total pigment (QT), and color density trait (CD). A total of 139 individuals were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…Li et al 38 showed that additive model and the combined additive and dominance models produced the majority of significant SNPs in feed-related traits. Recently, Darwish et al 39 demonstrated for eggshell blueness chickens that the contribution of genotypic effects of some SNPs were further divided into additive and dominant effects depending on the trait.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 38 showed that additive model and the combined additive and dominance models produced the majority of significant SNPs in feed-related traits. Recently, Darwish et al 39 demonstrated for eggshell blueness chickens that the contribution of genotypic effects of some SNPs were further divided into additive and dominant effects depending on the trait.…”
Section: Discussionmentioning
confidence: 99%
“…Using varieties of chicken genotypes, significant effects on genetic differences were found in yolk and albumen free amino acid contents. Until now, genome-wide association study (GWAS) and quantitative trait locus (QTL) mappings have been performed for egg traits such as egg weight, eggshell color, yolk size, and albumen height for identifying genetic variants [10][11][12][13][14]. However, there are few reports of GWAS and QTL studies for egg yolk and albumen amino acid traits so far [17].…”
Section: Plos Onementioning
confidence: 99%
“…Egg traits such as egg weight, eggshell color, yolk size, albumen height [10][11][12][13][14], and ingredients of yolk and albumen [15][16][17] are fairly influenced by genetic factors. Therefore, eggs from several breeds may express a large variation in the appearance of eggs and contents of yolk and albumen caused by differences in genetic background.…”
Section: Introductionmentioning
confidence: 99%
“…A cor azul da casca dos ovos exibe uma herança autossômica dominante e os ovos postos por aves homozigotas são mais azuis do que os ovos de heterozigotos . O gene autossômico dominante relacionado à cor azul da casca do ovo foi denominado Oocyan (locus O) e mapeado no braço curto do cromossomo 1 a uma distância de 2,3 cM do vírus endógeno da leucose aviária (ALEV1) (Bartlett et al, 1996;Bitgood et al, 2000 (Darwish et al, 2019;.…”
Section: Cor Da Cascaunclassified
“…Darwish et al (2019) identificaram uma região de 653,819 Kb no cromossomo 21 da galinha que está associada com características de intensidade da cor da casca do ovo. Esta região genômica contém os genes candidatos AJAP1, C1ORF174, CAMTA1, CEP104 e TNFRSF9, que foram significativamente associados a galinhas de ovos com casca azul escuro e azul claro.…”
unclassified